ON THE NEED TO PREPARE STUDENTS OF REGIONAL DEVELOPMENT FOR ADMINISTRATIVE AND ORGANIZATIONAL SKILLS - Kamen Petrov (Journal of Bio-Based Marketing, 2024)
The article deals with discussion problems and views of the author on the problems of the formation of qualities and skills of future specialists in the field of regional development based on the changed environment and new pattern of global integration and processes of regionalization of the world. Its focus is on preparing young regional development professionals for administrative work. The affiliation of the Regional Development specialty to the professional field of Administration and Management to enable education to focus on the opportunities for trainees to acquire newer and more competent knowledge and skills in the field of organization and management. This aspect of skill acquisition and the focus of the training is on knowledge and competencies in the public sector. Particular attention is given to the need for practical skills to prepare for work in private business organizations and management. An innovative pioneering model of work qualities and skills formation is proposed, which is also largely a matter of discussion and further modeling.